化简:2a-{5b+[2a-3b-(a-7a-5b)]}
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 12:04:27
化简:2a-{5b+[2a-3b-(a-7a-5b)]}化简:2a-{5b+[2a-3b-(a-7a-5b)]}化简:2a-{5b+[2a-3b-(a-7a-5b)]}原式=2a-{5b+[2a-3b
化简:2a-{5b+[2a-3b-(a-7a-5b)]}
化简:2a-{5b+[2a-3b-(a-7a-5b)]}
化简:2a-{5b+[2a-3b-(a-7a-5b)]}
原式=2a-{5b+[2a-3b-(-6a-5b)]}
=2a-[5b+(2a-3b+6a+5b)]
=2a-[5b+(8a+2b)]
=2a-(5b+8a+2b)
=2a-(8a+7b)
=2a-8a-7b
=-6a-7b
2a-{5b+[2a-3b-(a-7a-5b)]}
=2a-5b-[2a-3b-(a-7a-5b)]
=2a-5b-2a+3b+a-7a-5b
=-6a-7b
-6a-7b
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
化简a/b(a-b)-b/a(a-b)其中a=3 b=-2
(3a^2*b-7a*b^2-a^2*b^2)*5a*b化简
a^2+5(a-b)(a+b)-(3a-2b)^2+9b^2,化简
化简:7(a-b-c)-5(a+b-c)+3(a-b-c)+(a+b-2)
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
a+(5a-3b)-2(a-3b)化简
a-(5a-3b)+(2b-a)化简
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
计算(5a-3b)^2+(a+b)(a-b)
2a+b/3a+5b 求a/b
已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?
已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?
2a-(5b-a)+b化简
化简 (a+b)²+2a(a-1/2b)-3(a-b)(a+b)
5a-3b-a+2b
(a-2b)(5a+3b)